Climate law and developing countries legal and policy challenges for the world economy - Richardson, Benjamin J.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2009)
This timely book examines the legal and policy challenges in international, regional and national settings, faced by developing countries in mitigating and adapting to climate change.
pt. I. Climate justice -- pt. II. Expanding the scope of the climate change legal regimes -- pt. III. The clean development mechanism and mitigation strategies -- pt. IV. Climate policy bridging the north and south.
Includes bibliographic references and index.
Keywords: Climatic changes -- Law and legislation -- Developing countries; Climatic changes -- Economic aspects -- Developing countries; Global warming -- Law and legislation -- Developing countries; Climatic changes -- Government policy -- Developing countries; Environmental law, International; Electronic books